2008
DOI: 10.1002/jbm.a.32110
|View full text |Cite
|
Sign up to set email alerts
|

Elastomeric high‐mineral content hydrogel‐hydroxyapatite composites for orthopedic applications

Abstract: The design of synthetic bone grafts that mimic the structure and composition of bone and possess good surgical handling characteristics remains a major challenge. We report the development of poly(2-hydroxyethyl methacrylate) (pHEMA)-hydroxyapatite (HA) composites termed “FlexBone” that possess osteoconductive mineral content approximating that of human bone yet exhibit elastomeric properties enabling the press-fitting into a defect site. The approach involves crosslinking pHEMA hydrogel in the presence of HA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 39 publications
1
55
0
Order By: Relevance
“…24,25 Although hydrogel-ceramic scaffolds have not been explored for calcified cartilage regeneration, this type of composite scaffold has been tested for bone applications and shown to promote calcification in vitro. 26,27 For example, in a study by Patel et al, nanosized HA particles were incorporated in a cyclic acetal hydrogel with predifferentiated rat bone marrow stromal cells. 28 It was found that HA presence increased cell alkaline phosphatase (ALP) activity and promoted osteogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Although hydrogel-ceramic scaffolds have not been explored for calcified cartilage regeneration, this type of composite scaffold has been tested for bone applications and shown to promote calcification in vitro. 26,27 For example, in a study by Patel et al, nanosized HA particles were incorporated in a cyclic acetal hydrogel with predifferentiated rat bone marrow stromal cells. 28 It was found that HA presence increased cell alkaline phosphatase (ALP) activity and promoted osteogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Toward this end, we developed FlexBone, a structural composite with up to 50 wt% nHA structurally integrated within a hydroxylated crosslinked carbon network. 2 Despite its high mineral content, this structural composite can withstand repetitive functional-compressive loads with excellent shape recovery under physiological conditions. 2 As a result of the high surface area of the nHA component and its intrinsic affinity for proteins and small molecule therapeutics, 3,4 FlexBone is also a suitable vehicle for delivering growth factors and antibiotics in a sustained and localized manner in vitro (Supplementary Fig.…”
mentioning
confidence: 99%
“…ECM mimetic modifications and the provision of a nanocrystalline hydroxyapatite (nHAp)-rich micro-environment within synthetic hydrogels materials may be used to modulate specific cellular responses. 15 However, the development of an IPN biomaterial with both biological and synthetic components and ECM-mimetic modifications remains a significant challenge. A range of bioactive, inorganic nanoparticles such as nHAp, calcium phosphate, bioactive glasses and silica consist of minerals that are already present in the body, are necessary for the normal functioning of human bone tissue and have shown favourable biological responses.…”
Section: -10mentioning
confidence: 99%